COVID-19 and Mental Health—What Do We Know So Far? - dos Santos, Carolina Ferreira; Picó-Pérez, Maria; Morgado, Pedro (Frontiers in Psychiatry, 2020)
The Coronavirus Disease 2019 (COVID-19) pandemic brought several worldwide health, social and economic disturbances – particularly associated with the imposed confinement measures – that raised concerns about an emerging public mental health crisis. Studies investigating the early mental health impact of the pandemic on general population and vulnerable groups, such as healthcare workers, revealed a high prevalence of stress, anxiety and depression symptoms, among others, and found several risk and protective factors. Along with these findings, the risk of substance use, suicide, domestic violence, and complicated grief may increase. We further discuss interventions that can be applied at a governmental, institutional, and individual level to minimize the mental health consequences of the pandemic, such as using telehealth to provide remote support or practicing self-care. These interventions should be maintained after the initial outbreak, as current disturbances may impact long-term well-being. We encourage the development of longitudinal studies to assess long-term adaptive responses.